Genetic Characterization of Feline Parvovirus Isolate Fe–P2 in Korean Cat and Serological Evidence on Its Infection in Wild Leopard Cat and Asian Badger - Kim, Young Ji; Yoon, Sun-Woo; Jang, Jin Ho; Jeong, Dae Gwin; Lee, Beom Jun; Kim, Hye Kwon (Frontiers in Veterinary Science, 2021)
Feline parvovirus (FPV) is a small, non-enveloped, single-stranded DNA virus that infects cats. We recently isolated a feline parvovirus Fe-P2 strain from a dead stray cat in Iksan, 2017. Its partial genomic sequence (4,643 bases) was obtained, and phylogenetic analysis based on the VP2 nucleotide sequence showed that the FPV Fe-P2 strain was closely related to the FPV isolate Gigucheon in cat, 2017 (MN400978). In addition, we performed a serum neutralization (SN) test with the FPV isolates in various mammalian sera. These were from raccoon dog, water deer, Eurasian otter, Korean hare, leopard cat, and Asian badger, which were kindly provided by Chungnam Wild Animal Rescue Center. Notably, serological evidence of its infection was found in Asian badger, Meles leucurus (2/2) and leopard cat, Prionailurus bengalensis (5/8) through SN tests, whereas there was no evidence in raccoon dog, water deer, Eurasian otter, and Korean hare based on the collected sera in this study. These findings might provide evidence for the possible interspecies transmission of FPV among wild leopard cat and Asian badger in Korea. There should be additional study to confirm this through direct detection of FPVs in the related animal samples.